2020
DOI: 10.18332/tid/127524
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors for depression, suicidal ideation and suicide attempt among asthmatic adolescents with experience of electronic cigarette use

Abstract: INTRODUCTION While electronic cigarette (EC) use is rapidly increasing among asthmatic adolescents, little is known about the links between EC use and depression or suicidality. We assessed associated factors for depression and suicidality in asthmatic adolescents with experience of EC use. METHODS We analyzed the data from the 11th to 13th Korea Youth Risk Behavior Web-based Surveys, which were completed from 2015 to 2017. Data were obtained from a stratified, multista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Moreover, EC use was associated with lower general health scores, higher breathing difficulty scores and a greater proportion of reporting asthma [ 95 ]. A large epidemiological study in USA with a weighted sample size of 31,721,603 adults between 18 and 24 years (2,503,503 with former and 3,200,681 with current asthma) found that the prevalence of EC use was significantly higher among young adults with current or former asthma and that asthma combined with EC use was significantly associated with worse mental health [ 96 ], a finding similar to that of another study from Korea [ 72 ].…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Moreover, EC use was associated with lower general health scores, higher breathing difficulty scores and a greater proportion of reporting asthma [ 95 ]. A large epidemiological study in USA with a weighted sample size of 31,721,603 adults between 18 and 24 years (2,503,503 with former and 3,200,681 with current asthma) found that the prevalence of EC use was significantly higher among young adults with current or former asthma and that asthma combined with EC use was significantly associated with worse mental health [ 96 ], a finding similar to that of another study from Korea [ 72 ].…”
Section: Resultsmentioning
confidence: 59%
“…Several investigators have concluded that EC could be associated with the development of pulmonary disorders, including asthma and might increase asthma severity and exacerbations [ 18 , 31 , 61 , 62 , 63 , 64 ]. Numerous cross-sectional studies with a large number of participants have described the significant association between EC use and even secondhand exposure and asthma diagnosis and severity [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], compared to the few studies which found no association [ 75 , 76 ], or even negative association between EC use and asthma [ 77 , 78 ]. A prospective cohort study also found that EC use was associated with an increased risk of developing respiratory disease, including asthma, independent of cigarette smoking [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Illness uncertainty may be an important factor that influences psychological functioning and distress and coping in the context of pediatric chronic illness [33]. Adolescents reported predominantly negative feelings associated with their symptoms such as afraid, challenging, difficulty, frustration, panic, scared, sad, upset, and like crap [34]; frustration, being left out, anger, worry, concern, discomfort, and fear from asthma attacks [15]; arguing, bullying and sad feeling had lower flourishing [42]; and depression and suicidality [35]. These conditions must be managed wisely in order to keep a strong mind for treating the disease and their symptoms [36].…”
Section: Feelings Of Uncertaintymentioning
confidence: 99%